Review of the Sedimentological and Geochemical Approaches for Environmental Assessment of River Sadong, Samarahan-Asajaya District Sarawak, Malaysia - Omorinoye, Omolayo Ajoke; Zaini, Assim; Ismail, Jusoh; Durumin Iya, Naseer Inuwa; Umaru, Isaac John (Technoscience Publications, 2019)
This paper presents an overview of the implication of geomorphology and sedimentology on the chemical characteristics of sediments of River Sadong, Malaysia. There is limited published work on the effect of topography, climate, soil and geology on the sediments lying in the River Sadong. Studies have been undertaken around Kota Samarahan and Asajaya areas whereby some heavy metal constituents and their environmental effects were determined. The study entails the description of the depositional processes alonggside with physical and geochemical changes, without neglecting natural and anthropogenic effects.